2023
DOI: 10.3390/healthcare11131889
|View full text |Cite
|
Sign up to set email alerts
|

The Casual Association Inference for the Chain of Falls Risk Factors-Falls-Falls Outcomes: A Mendelian Randomization Study

Abstract: Previous associations have been observed not only between risk factors and falls but also between falls and their clinical outcomes based on some cross-sectional designs, but their causal associations were still largely unclear. We performed Mendelian randomization (MR), multivariate Mendelian randomization (MVMR), and mediation analyses to explore the effects of falls. Our study data are mainly based on White European individuals (40–69 years) downloaded from the UK Biobank. MR analyses showed that osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
3
1
Order By: Relevance
“…The fact that the frequency of walking aid use was much higher in our study also strengthens this hypothesis. It has already been observed in studies that the presence and degree of frailty is closely related to falls (14). We did not find a statistically significant difference between the old and the oldest old in terms of history of fall (p=0.714), while fear of falling was significantly higher in the oldest old group (p=0.007).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The fact that the frequency of walking aid use was much higher in our study also strengthens this hypothesis. It has already been observed in studies that the presence and degree of frailty is closely related to falls (14). We did not find a statistically significant difference between the old and the oldest old in terms of history of fall (p=0.714), while fear of falling was significantly higher in the oldest old group (p=0.007).…”
Section: Discussioncontrasting
confidence: 69%
“…In our study, we demonstrated that falls occur more frequently with increasing age. Advanced age is an important risk factor for falls (14). With increasing age, changes in the neuromuscular system, malnutrition, geriatric syndromes such as sarcopenia, and visual problems occur and cause falls (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have affirmed significantly correlation between genetically determined body mass index (BMI) and the initiation of smoking (whether an individual had ever smoked regularly) with the risk of falls [ 27 , 28 ]. BMI and smoking initiation are modifiable factors in daily life.…”
Section: Methodsmentioning
confidence: 99%
“…In China, the prevalence ranges from 0.89% to 17.23% among people aged 18 to 75 [3]. Osteoporosis can lead to falls, and there is a certain causal relationship between them [4]. A systematic analysis of the Global Burden of Disease Study 2021 indicated that falls are one of the leading causes of age-standardized mortality globally, with 9.9 deaths per 100,000 people [5].…”
Section: Introductionmentioning
confidence: 99%